Personal inventory management system - Sng, Aaron Zhi Wei (2017)
Forgetting one’s personal artifact proves to be troublesome and vexing especially when one is in a rush. Forgetfulness can be attributed but not limited to stress and old-age. In Singapore where the workforce faces a high amount of stress and the trend of increase in the ageing population. The problem of forgetting one’s personal artifact is an important one that we should solve. Smartphones have become a commonplace item with the smartphone penetration in Singapore being ranked the highest globally with nine out of ten persons in the workforce having access to a smartphone. The objective of this Final Year Project is to design and develop a personal inventory management system. This system consists of an Android application as the front-end and a Web Server built on the Laravel framework as a back-end. With the application, one can record details about where one has placed a personal artifact and categorize them. Additional input methods such as image and voice recording upload make it easier for users to describe where the artifact is. The project was carried out with the Agile Development Methodology and made use of Use Case Specifications, Activity Diagrams and the ER Diagram. The application was average in usefulness according to a survey done, however the sample size is too small to conclude an accurate evaluation. Recommendations for future implementation is the processing of the data in the database to produce a list of most common places that an item is placed. This can be used to do a suggestion feature for where a personal artifact might be found.